Production of bio oil from sweet lime empty fruit bunch by pyrolysis. (February 2020) - Sukumar, V.; Manieniyan, V.; Senthilkumar, R.; Sivaprakasam, S.
Abstract: In this paper, the bio oil is obtained from sweet lime empty fruit bunch as feedstock using fixed bed reactor. The experimental study is to analyze the impacts of feedstock size, temperature and flow rate of nitrogen gas on the bio oil yield. The feed stock size, temperature and nitrogen gas flow rate were varied from 2 mm, 4 mm and 6 mm, 500 °C, 550 °C and 600 °C, 0.2 lit/min, 0.3 lit/min and 0 .4. lit/min respectively. The rate of heating used was 10 °C/min used. The bio oil yield maximum acquired was 28.3% with bio-char yield of 25.7% and 27.8% of gas at a size of 4 mm, flow rate of nitrogen gas 0.3 lit/min and 550 °C temperature was optimal. The properties investigated for the bio oil include both physical and chemical. The bio oil characteristics were analyzed with the help of GCMS. Highlights: Bio oil is prepared using Sweet Lime Empty Fruit Bunch By Pyrolysis. Effects of bio mass size and Temperature were studied. The bio oil was analyzed using GC-MS. The feed stock size of 4 mm and 550 °C temperature was optimal.